A survey of team culture and learning organization in the resuscitation of neonates with congenital anomalies: A single center experience - Anna Bostwick; Anne Ades; Carolina Rodriguez-Paras; Madeline Dombroski; Charis Lim; Maria Ordoñez Paredes; Lauren Heimall; Leane Soorikian; Sara C. Handley; Heidi M. Herrick (Resuscitation Plus)
Aim: Delivery room resuscitation of neonates with congenital anomalies is complex. This study aimed to assess survey psychometrics and measure learning organization culture among resuscitation team members in a pediatric hospital delivery room dedicated to neonates with congenital anomalies. Methods: We administered the Short-Form Learning Organization Survey with the addition of an open-ended question to all delivery room resuscitation team members from 5/2023 to 7/2023. Psychometric properties were assessed to confirm the survey’s reliability and validity in the delivery room context. Total and subscale scores were calculated, and differences were assessed by clinical role. The open-ended qualitative data were analyzed using an inductive approach and coded for theme and valence (positive, negative, neutral). Results: The response rate was 52% (159/307) with all roles represented. Psychometric assessment produced a 25-item survey with high reliability and validity. There were no differences in total scores across roles. Nurses had higher scores compared to attending physicians (p < 0.01) and advanced practice providers (p < 0.05) for the supportive learning environment subscale, and advanced practice providers (p < 0.05) for the training subscale after multiple comparisons adjustment. Qualitative analysis revealed seven themes: time constraint, environment, adequate staffing, different opinions, care deviations, leadership, and training. Valence analysis showed variation by role, with more positive nursing responses. Conclusion: The refined 25-item Short-Form Learning Organization Survey is a reliable and valid measure of learning organization culture for neonatal resuscitation teams. Differences in subscale scores and qualitative valence across roles highlight opportunities to improve interprofessional learning organization and team culture.